Serotypic diversity and sequence variation of the ompA gene among Mannheimia haemofytica isolates from domestic ruminants - VOUGIDOU (Χ. ΒΟΥΓΙΔΟΥ) C.; SANDALAKIS (Β. ΣΑΝΤΑΛΑΚΗΣ) V.; PSAROULAKI (Α. ΨΑΡΟΥΛΑΚΗ) A.; PETRIDOU (Ε.Ι. ΠΕΤΡΙΔΟΥ) E.; DONACHIE, W.; EKATERINIADOU (Λ.ΑΙΚΑΤΕΡΙΝΙΑΔΟΥ) L. (Journal of the Hellenic Veterinary Medical Society, 2017)
Pneumonia caused by Mannheìmia haemolytica is an important disease of ruminants. Because of its economic significance, several methods have been used to study the pathogenicity and epidemiology of M. haemolytica. The objectives of this study were to provide data about the prevalence of the different serotypes of the bacterium and to investigate the genetic diversity of a significant virulence factor, the ompA gene. Two methods, DNA sequencing analysis and DGGli, were used to study the polymorphisms of the ompA gene. Ninety-four isolates from pneumonic lungs were investigated. Capsular scrotyping showed that serotype Λ2 was the predominant serotype among ovine strains and the only serotype found in caprine strains. This is the first reported analysis of the ompA gene of M haemolytica strains isolated from goats. Analysis of the gene revealed five DGGli patterns and nine genotypic groups. The ovine isolates, which belonged to four DC G li patterns, showed a much greater diversity than the caprine strains, which belonged to just two DGGF patterns, Sequence analysis was used to verify the DGGE results and revealed eight genotypic groups among the ovine isolates and three among the caprine ones. Furthermore, the correlation of these results showed a great diversity of the ompA gene among serotype A2 isolates.